Tinjauan Hak Eksklusif Atas Potret Yang Dipergunakan Secara Komersil Berdasarkan Undang-Undang Nomor 28 Tahun 2014 - Helena Damai Ratih; R. Rahaditya (Jurnal Hukum Adigama, 2022)
Exclusive rights to commercial used portraits are a part of the copyright law that is regulated in Law Number 28 of 2014 on Copyright. According to Article 11 paragraph (1) of Law No. 28 of 2014, the creator or copyright owner is entitled to the exclusive right to announce or reproduce their creation, including the exclusive right to portraits used commercial. Exclusive rights to commercial used portraits are rights that give the creator or copyright owner the authority to regulate the use of the portrait by others. This is intended to prevent the use of portraits without the knowledge or consent of the creator or copyright owner. In addition, exclusive rights to commercial used portraits also give the creator or copyright owner the right to receive remuneration for the use of the portrait. The remuneration can be in the form of royalties or a sum of money that must be paid by the party using the portrait for commercial purposes. To prevent the use of portraits without the knowledge or consent of the creator or copyright owner, Law No. 28 of 2014 regulates violations of copyright. Article 31 paragraph (1) of Law No. 28 of 2014 states that anyone who intentionally or without rights announces or reproduces the work of others without the permission of the creator or copyright owner can be subject to criminal sanctions or fines.